Children's understanding of when a person's confidence and hesitancy is a cue to their credibility. - Susan A J Birch; Rachel L Severson; Adam Baimel (PLoS ONE, 2020)
The most readily-observable and influential cue to one's credibility is their confidence. Although one's confidence correlates with knowledge, one should not always trust confident sources or disregard hesitant ones. Three experiments (N = 662; 3- to 12-year-olds) examined the developmental trajectory of children's understanding of 'calibration': whether a person's confidence or hesitancy correlates with their knowledge. Experiments 1 and 2 provide evidence that children use a person's history of calibration to guide their learning. Experiments 2 and 3 revealed a developmental progression in calibration understanding: Children preferred a well-calibrated over a miscalibrated confident person by around 4 years, whereas even 7- to 8-year-olds were insensitive to calibration in hesitant people. The widespread implications for social learning, impression formation, and social cognition are discussed.